Assessing Metabolism and Injury in Acute Human Traumatic Brain Injury with Magnetic Resonance Spectroscopy: Current and Future Applications - Stovell, Matthew G.; Yan, Jiun-Lin; Sleigh, Alison; Mada, Marius O.; Carpenter, T. Adrian; Hutchinson, Peter J. A.; Carpenter, Keri L. H. (Frontiers in Neurology, 2017)
Traumatic brain injury triggers a series of complex pathophysiological processes. These include abnormalities in brain energy metabolism; consequent to reduced tissue pO2 arising from ischaemia or abnormal tissue oxygen diffusion, or due to a failure of mitochondrial function. In-vivo magnetic resonance spectroscopy (MRS) allows non-invasive interrogation of brain tissue metabolism in patients with acute brain injury. Nuclei with ‘spin’ e.g. 1H, 31P and 13C, are detectable using MRS and are found in metabolites at various stages of energy metabolism, possessing unique signatures due to their chemical shift or spin-spin interactions (J-coupling). The most commonly used clinical MRS technique, 1H MRS, uses the great abundance of hydrogen atoms within molecules in brain tissue. Spectra acquired with longer echo-times include N-acetylaspartate, creatine and choline. N-acetylaspartate, a marker of neuronal mitochondrial activity related to ATP, is reported to be lower in patients with TBI than healthy controls, and the ratio of N-acetylaspartate/creatine at early time points may correlate with clinical outcome. 1H MRS acquired with shorter echo-times produces a more complex spectrum, allowing detection of a wider range of metabolites. 31P MRS detects high energy phosphate species, which are the end-products of cellular respiration: adenosine triphosphate (ATP) and phosphocreatine. ATP is the principal form of chemical energy in living organisms, and phosphocreatine (PCr) is regarded as a readily-mobilised reserve for its replenishment during periods of high utilisation. The ratios of high energy phosphates are thought to represent a balance between energy generation, reserve and use in the brain Additionally, the chemical shift difference between Pi and PCr enables calculation of intracellular pH. 13C MRS detects the 13C-isotope of carbon in brain metabolites. As the natural abundance of 13C is low (1.1%),13C MRS is typically performed following administration of 13C-enriched substrates which permits tracking of the metabolic fate of the infused 13C in the brain over time, and calculation of metabolic rates in a range of biochemical pathways, including glycolysis, the tricarboxylic acid (TCA) cycle, and glutamate-glutamine cycling. The advent of new hyperpolarization techniques to transiently boost signal in 13C-enriched MRS in-vivo studies shows promise in this field and further developments are expected.